Exacerbation and functional capacity of patients with COPD undergoing an exercise training program: longitudinal study - Diego Marmorato Marino; Kamilla Tays Marrara; Juliano Ferreira Arcuri; Cecília Candolo; Mauricio Jamami; Valéria Amorim Pires Di Lorenzo
Objective To analyze if there is influence of body weight, body mass index (BMI), body composition, dyspnoea, grip strength and tolerance to exertion in the occurrence of exacerbation during a 12-month follow up of patients with COPD who underwent a physical training program. Material and methods Sixty three patients were distributed in two groups, (Exacerbation Group - EG, n = 29; Non-Exacerbated Group - NEG, n = 34). The Mann Whitney test was used for the comparison between groups, the Friedman test (posthoc Dunn) to compare the assessments and the logistic regression analysis, with a significance level of p < 0.05. Results There is a significant difference between the groups in age and walked distance (WD) in the sixminute walk test (6MWT). The WD was reduced in 6th, 9th and 12th month revaluation compared to baseline and 3 months for the EG. Logistic regression analysis showed a significant interaction between the lean body mass and the WD, BMI with the lean body mass and the BMI with the WD, this and the isolated dyspnoea, and lean body mass with body weight. Conclusion Involving several variables along the follow up of patients with COPD in physical therapy programs is important, since it may prevent or reduce the chance of the occurrence of exacerbations. In addition, older patients with less tolerance to physical activity had a higher number of episodes of exacerbation, even when participating in a physiotherapy program associated to exercise training.